Elastic antibacterial membranes comprising particulate laden fibers for wound healing applications. Issue 8 (4th October 2018) - Li, Y.; Zhang, C.; Zhu, L.‐F.; Ahmad, Z.; Li, J.‐S.; Chang, M.‐W.
ABSTRACT: Medicated skin care products are available in various forms; ranging from lotions and creams to bandages and membranes. In this study, antibacterial particulate laden fibrous membranes (FMs) were prepared via electrospraying of tetracycline hydrochloride‐loaded poly(ε‐caprolactone) particles alongside electrospinning of thermoplastic polyurethane (TPU) fibers, through which both mechanical and biological aspects of a complete membrane system can be achieved. Random (R) and ordered (P and V) patterns of TPU FMs were afforded using a rotating collector. Water contact angle and bacterial inhibition zone tests were performed to assess suitability of the system specifically for wound care. Stress–strain and in vitro drug release tests were performed to assess suitability of newly developed systems specifically for hybrid membranes (HMs). The highest tensile strength (32.1 ± 4.9 MPa) with elasticity (104.2 ± 6.0%) and the most sustained release rate indicate HMs (P) are potentially suitable materials for wound‐care applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47105. Abstract :